The Effect of Capital Structure, Liquidity, Dividend Policy, and Debt Policy on Company Value with Profitability as Moderating Variables in the Jakarta Islamic Index for the 2016-2020 Period - Yulia Swantika Tanjung; Tri Widyastuti; Widarto Rachbini (Financial Management Studies, 2021)
This study is to see the effect of Capital Structure, Liquidity, Dividend Policy and Debt Policy on Firm Value and will later be moderated by Profitability of companies listed on the Jakarta Islamic Index for the 2016-2020 period. This study uses a quantitative and descriptive approach with a population of all companies listed on the Jakarta Islamic Index (JII) as many as 30 companies, so that a sample with the number of data observations (N) is 70 observations for each variable (14 companies x 5 years). research period). The type of secondary data with data sources is the company's website and also www.idx.go.id. The data analysis technique is Multiple Linear Regression Analysis using SPSS software. The research findings show: 1) Capital structure, liquidity, dividend policy, debt policy and profitability have a significant effect on firm value. 2) Profitability acts as a moderator in the influence of capital structure, liquidity, dividend policy, and debt policy on firm value. Keywords: Capital Structure, Liquidity, Dividend Policy, Debt Policy, Profitability, Firm Value